Concurrence of dermatomyositis and psoriasis: a case report and literature review - Chu, Dan; Yang, Wei; Niu, Jun (Frontiers in Immunology, 2024)
Dermatomyositis (DM) is a type of inflammatory myopathy with unknown causes. It is characterized by distinct skin lesions, weakness in the muscles close to the body, and the potential to affect multiple organs. Additionally, it may be associated with the presence of malignancies. The development of DM is influenced by genetic susceptibility, autoimmune response, and various external factors like cancer, drugs, and infectious agents. Psoriasis is a chronic, recurring, inflammatory, and systemic condition. Scaly erythema or plaque is the typical skin manifestation.The etiology of psoriasis involves genetic, immune, environmental and other factors. It is uncommon for a patient to have both of these diseases simultaneously, although individuals with DM may occasionally exhibit symptoms similar to those of psoriasis. Our patient was diagnosed with psoriasis in his 50s because of scalp squamous plaques, but he did not receive standard treatment. Ten years later, he developed symptoms of muscle pain and limb weakness. He was diagnosed with psoriasis complicated with dermatomyositis in our department and received corresponding treatment. Moreover, we reviewed the relevant literature to evaluate similarities and differences in clinical manifestation and treatment to other cases.